Penerapan Business Intelligence & Online Analytical Processing untuk Data-Data Penelitian dan Luarannya pada Perguruan Tinggi Menggunakan Pentaho - Hasan, Firman Noor; Sudaryana, I Ketut (Infotech: Journal of Technology Information, 2022)
Utilization of ICT in various sectors is needed, especially those related to business impact and strategy. Information technology is the backbone of the sustainability of businesses, companies, and organizations. Companies that are able to utilize ICT well, therefore indirectly adapt to the times and strive to excel from competitors. The method used refers to the steps recommended by Carlo Vercellis. The software and tools used are open source based, such as Pentaho Data Integration for processing extract, transform, load (ETL), Pentaho Community Edition for dashboards, Pentaho Report Designer for report generation, and Mondrian OLAP for displaying multidimensional data. The results of this study conclude application of business intelligence in universities is very easy and efficient, the use of a dashboard that is presented visually and interactively is very helpful for leaders in viewing existing research data. So it is very helpful for organizations, especially university leaders in making decisions.